Historic Preservation in Turkey and the United States: a Cross-Cultural Comparison (Prostor, 2022)
The research examines and compares the various roles of governmental and non-governmental organizations (NGOs) in Turkey and the United States, aiming to assess how they shaped the preservation field and their potential knowledge transfer values. The study was conducted in governmental archives, official websites of related organizations and through oral communication and literature surveys related to preservation foundations, NGOs, and waqfs in both countries - with different national, historic, religious, and cultural characteristics. The parameters used as cross-cultural comparison included primary actors and main legislations in preservation both in history and at present. The research has revealed that the waqf system in Turkey has a deep-rooted historic, religious, and socio-cultural context, and differs from the preservation foundations in the USA in many respects. Yet, the foundations established in and after the 20th century in Turkey and the preservation activities of foundations in both countries also share similar motives, stimuli, and objectives to preserve both natural/cultural heritage and cross-cultural comparisons suggest that they may learn from each other by knowledge transfer.